MONITORING THE MATURITY OF AHMEUR BOUAMER AUTOCHTONOUS VARIETY AND DETERMINING OF THE OPTIMUM HARVEST DATE - Ghouila, Z; Baaliouamer, A (university of eloued -جامعة الوادي, 2022)
Morphological ampelography characteristics, technological, phenolic and tannic maturities were studied over four seasons (from 2009 to 2012) of Ahmeur Bouamer autochtonous Algerian variety. During the four harvests, Ahmeur Bouamer's cluster has showed a high quality of morphological parameters (weight, size, number of seeds/ berries per cluster).The weight was proportional to the size of the cluster which was moderately compact, thus avoiding the deformation and the bursting of the berries. As For the maturity index (MI), Ahmeur Bouamer grape recorded values ranging from 31.07 to 54.95 for the four seasons; values which would make it possible to consider that the harvest would be of excellent quality (when 30 <MI <50). As well as for total anthocyanin potential (TAP) exceeding 1000 mg / L and total polyphenol index (TPI) with values greater than 50, these values confirm that the cluster presents high level of maturity. The monitoring of the MI every week in the phase of ripening (september-october) for 2010 and 2011 have showed that the maximum ripeness index was reached on September 27th with highest level of maturity for both harvests, date that can be considered by the winemaker as optimal date of harvest.
article
Keywords: Ahmeur Bouamer; phenolic maturity; harvest; maturity index; harvest date.